The atherogenic index of plasma is a strong and independent predictor for coronary artery disease in the Chinese Han population. Issue 37 (September 2017) - Cai, Gaojun; Shi, Ganwei; Xue, Sheliang; Lu, Wei
Abstract : Abstract: Dyslipidemia is one of the most important factors for coronary artery disease (CAD). The atherogenic index of plasma (AIP), a new comprehensive lipid index, might be a strong marker for predicting the risk of CAD. A hospital-based case–control study including 2936 CAD patients and 2451 controls was conducted in a Chinese population. Traditional lipid parameters were detected, and nontraditional lipid comprehensive indexes were calculated. Compared with controls, CAD patients had higher levels of total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C). By contrast, the level of high-density lipoprotein cholesterol (HDL-C) was lower in CAD patients. The values of nontraditional lipid profiles, including non-HDL-C, TC/HDL-C, LDL-C/HDL-C, non-HDL-C/HDL-C (atherogenic index, AI), TC*TG*LDL/HDL-C (lipoprotein combine index, LCI), and lg (TG/HDL-C) (AIP), were all significantly higher in the cases than in the controls. The results of Pearson correlation analyses indicated that AIP was positively and significantly correlated with TC ( r  = 0.125, P  < .001), TG ( r  = 0.810, P  < .001), LDL-C ( r  = 0.035, P  < .001), non-HDL-C ( r  = 0.322, P  < .001), TC/HDL-C ( r  = 0.669, P  < .001), LDL-C/HDL-C ( r  = 0.447, P  < .001), AI ( r  = 0.669, P  < .001), and LCI ( r  = 0.688, P  < .001) and was negatively correlated with age ( r  = −0.122, P  < .001) and HDL-C ( r  = −0.632, P  < .001). In the univariate logistic regression analysis, AIP was the lipid parameter that was most strongly associated with CAD, with an unadjusted odds ratio of 1.782 (95% confidence interval: 1.490–2.131, P  < .001), for an increase of 1-SD. Multivariate logistic regression analyses revealed that AIP was an independent risk factor for CAD. AIP might be a strong and independent predictor for CAD in the Chinese Han population.